2021
DOI: 10.3390/ijms221810011
|View full text |Cite
|
Sign up to set email alerts
|

Key Physicochemical Determinants in the Antimicrobial Peptide RiLK1 Promote Amphipathic Structures

Abstract: Antimicrobial peptides (AMPs) represent a skilled class of new antibiotics, due to their broad range of activity, rapid killing, and low bacterial resistance. Many efforts have been made to discover AMPs with improved performances, i.e., high antimicrobial activity, low cytotoxicity against human cells, stability against proteolytic degradation, and low costs of production. In the design of new AMPs, several physicochemical features, such as hydrophobicity, net positive charge, propensity to assume amphipathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In our previous studies, the structural characterization as well as the antibacterial and antifungal activities of the peptides 1018-K6, MTP1, RiLK1, and RiLK3 were demonstrated [42][43][44][45][46], thus leading to investigations of their possible antiviral effects that have not been studied so far, considering that the ultimate goal of research is to find agents that exhibit a broad-spectrum antimicrobial activity and are therefore attractive for manufacturing applications. Moreover, two further peptides were considered in our study to expand the panel of potential antiviral compounds (Table 1), the newly designed RiLK30 and the already-known HIV inhibitor AVP2 [47], which was used as a reference.…”
Section: Peptide Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, the structural characterization as well as the antibacterial and antifungal activities of the peptides 1018-K6, MTP1, RiLK1, and RiLK3 were demonstrated [42][43][44][45][46], thus leading to investigations of their possible antiviral effects that have not been studied so far, considering that the ultimate goal of research is to find agents that exhibit a broad-spectrum antimicrobial activity and are therefore attractive for manufacturing applications. Moreover, two further peptides were considered in our study to expand the panel of potential antiviral compounds (Table 1), the newly designed RiLK30 and the already-known HIV inhibitor AVP2 [47], which was used as a reference.…”
Section: Peptide Designmentioning
confidence: 99%
“…We have recently demonstrated the antibacterial activity of a panel of designed AMPs against food pathogen contaminants, including Gram-positive and Gram-negative bacteria and fungi but not viruses [42][43][44][45][46]. The structural properties and mechanism of action of these peptides have been elucidated previously and these compounds were also found to be non-cytotoxic [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new 10-amino acid peptide, namely RiLK1 ( Agrillo et al, 2020 ; Falcigno et al, 2021 ), was designed based on the dodecapeptide 1018-K6 ( Palmieri et al, 2018 ; Colagiorgi et al, 2020 ; Festa et al, 2021 ; Ambrosio et al, 2022 ), a compound derived from a bovine HDP (host defence peptide) bactenecin, belonging to the cathelicidins family. Structural and functional analysis, revealed that RiLK1 is extremely active toward fungi, viruses, Gram-positive and-negative bacteria at low micromolar concentrations, showing no effects on human cell lines investigated in terms of viability and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic amino acids (lysine/arginine) provide the initial electrostatic interaction with the negatively charged membrane surfaces of the microbes [ 16 ]. Aromatic residues such as phenylalanine and tryptophan play important roles in antimicrobial and hemolytic activities as they facilitate the formation of amphipathic structures and are fundamental for the interaction at the interface between the aqueous solution and the hydrophobic membrane bilayer [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%